Role of Education in Changing Health Behaviour of Mothers - Chaudhary, Kumari Sita (Journal of Gurubaba, 2024)
Education is a life long journey for every person. Education in its general sense is a form of learning in which the knowledge, skills and habits of a group of people are transformed from one generation to the next generation. Education and health behaviour are two parts of the same coin where educated mother takes healthy behaviour. Education could affect the mother's health behaviours. Level of health is determined through human behavior; especially behavior is shaped through life style, culture, religion, education, and other multiple factors. Out of them education is one of the most important variable. This research entitled "Role of Education in Changing Health Behaviour of Mothers" has been prepared. The objective of this research is to find out health behaviours and to assess the role of education in changing health behaviour of the mothers. This study was based on descriptive research design and its nature was quantitative. The collected data were analyzed and interpreted using simple statistical tools like numerical and percentage with the help of cross sectional table. This study was found that highest (98.33%) of the respondents regularly cleaned teeth. Majority (51.67%) of the respondents had first child birth at the age of less than twenty. The least (7.50%) of the respondents had taken smoking who had illiterate and low level education. Education has some role on teeth cleaning and education has major role on using nail cutting devises, first child bearing and smoking. So, education has vital role in changing health behaviour of mothers.